DETEKSI GEN tlh DAN tdh PADA Bakteri Vibrio parahaemolyticus DARI AIR TAMBAK UDANG VANNAME (Litopenaeus vannamei) DI KABUPATEN REMBANG - Adila Nawan Hasrimi; Anto Budiharjo; Siti Nur Jannah (Jurnal Akademika Biologi, 2017)
Vibrio parahaemolyticus is hallophilic gram-negative bacteria that live as natural inhabitant in aquatic environment. All Vibrio parahaemolyticus strain known to have thermolabile hemolysin encoded by tlh gene as species marker. Thermostable direct hemolysin encoded by tdh gene is responsible for regulating one of the virulence factors in Vibrio parhaemolyticus. The aim of this research is to detect tlh gene and tdh gene from water of vanname shrimp’s aquaculture in Rembang regency. Colonies of green-blueish bacteria grew from the isolation of  vanname shrimp’s aquaculture water in CD-VP media which is identified as Vibrio parahaemolyticus. The isolated bacteria is specifically identified as Vibrio parahaemolyticus bacteria by the detection of tlh gene. Molecular analysis shows tdh negative result that indicates tdh gene is not present in the isolated bacteria. Vibrio parahaemolyticus isolate were cultured in Wagatsuma agar for the tdh gene confirmation test that showed Kanagawa negative result, in which indicated that V. parahaemolyticus did not produce thermostable direct hemolysin. Vibrio parahaemolyticus isolate did not show any virulence factors to initiate host colonization in the aquatic environment. Keywords: Vibrio parahaemolyticus, tdh gene, tlh gene